Differential abundance of microRNAs in seminal plasma extracellular vesicles (EVs) in Sahiwal cattle bull related to male fertility - Chauhan, Vitika; Kashyap, Poonam; Chera, Jatinder Singh; Pal, Ankit; Patel, Aditya; Karanwal, Seema; Badrhan, Shiva; Josan, Fanny; Solanki, Subhash; Bhakat, Mukesh; Datta, Tirtha Kumar; Kumar, Rakesh (Frontiers in Cell and Developmental Biology, 2024)
Sahiwal cattle, known for their high milk yield, are propagated through artificial insemination (AI) using male germplasm, largely contingent on semen quality. Spermatozoa, produced in the testes, carry genetic information and molecular signals essential for successful fertilization.Seminal plasma, in addition to sperm, contains nano-sized lipid-bound extracellular vesicles (SP-EVs) that carry key biomolecules, including fertility-related miRNAs, which are essential for bull fertility. The current study focused on miRNA profiling of SP-EVs from high-fertile (HF) and low-fertile (LF) Sahiwal bulls. SP-EVs were isolated using size exclusion chromatography (SEC) and characterized by dynamic light scattering (DLS) and nanoparticle tracking analysis (NTA). Western blotting detected the EV-specific protein markers TSG101 and CD63. The DLS analysis showed SP-EV sizes of 170-180 nm in HF and 130-140 nm in LF samples. The NTA revealed particle concentrations of 5.76 × 10 10 to 5.86 × 10 11 particles/ml in HF and 5.31 × 10 10 to 2.70 × 10 11 particles/ml in LF groups, with no significant differences in size and concentration between HF and LF. High-throughput miRNA sequencing identified 310 miRNAs in SP-EVs from both groups, with 61 upregulated and 119 downregulated in HF bull. Further analysis identified 41 miRNAs with significant fold changes and p-values, including bta-miR-1246, bta-miR-195, bta-miR-339b, and bta-miR-199b, which were analyzed for target gene prediction. Gene Ontology (GO) and KEGG pathway analyses indicated that these miRNAs target genes involved in transcription regulation, ubiquitin-dependent endoplasmic reticulum-associated degradation (ERAD) pathways, and signalling pathways.Functional exploration revealed that these genes play roles in spermatogenesis, motility, acrosome reactions, and inflammatory responses. qPCR analysis showed that bta-miR-195 had 80% higher expression in HF spermatozoa compared to LF, suggesting its association with fertility status (p<0.05). In conclusion, this study elucidates the miRNA cargoes in SP-EVs as indicators of Sahiwal bull fertility, highlighting bta-miR-195 as a potential fertility factor among the various miRNAs identified.